Improving Learning Outcomes of SD Negeri 4 Sembawa Students on Materials in Various Styles of Science Subjects Using Demonstration Methods - Rahayu, Santi Utami (PPSDP International Journal of Education, 2024)
This research was motivated by low student learning outcomes and not meeting the specified minimum completeness criteria, namely ≥70. This research aims to improve the learning outcomes of Class IV students at SDN 4 Sembawa in science subjects with various styles of material using the demonstration method. The research subjects were class IV with a total of 25 students. The implementation of this learning improvement uses the classroom action research stages which consist of design, implementation, data collection and reflection in two cycles, namely Cycle I and Cycle II. This research succeeded in increasing the average student scores from cycle I and cycle II. In cycle I there were several students who did not exceed the minimum completeness criteria, namely 8 students with a ratio of 32%, while 17 students exceeded the minimum completeness criteria with a ratio of 68%. In cycle II, many students did not exceed the minimum completeness criteria, namely 3 students with a ratio of 12%, while 22 students exceeded the minimum completeness criteria with a ratio of 88%. These results show that by using the demonstration method, students’ science learning outcomes increase.